Pengaruh Motivasi Belajar, Sarana dan Prasarana dan Lingkungan Keluarga terhadap Kemandirian Belajar dengan Efikasi Diri sebagai Variabel Mediasi - Anggraini, Shinta Dewi; Tusyanah, Tusyanah (Business and Accounting Education Journal, 2023)
The purpose of this study was to examine the influence of learning motivation, facilities and infrastructure, and the family environment on learning independence with self-efficacy as a mediating variable. The type of research used in this research is quantitative. Data was collected by questionnaire and analyzed using SEM-PLS. The population in this study were 134 students majoring in office administration education at UNNES in 2022. The sampling technique uses a saturated sample technique with descriptive analysis and inferential analysis methods. The results showed that of the 7 (seven) hypotheses proposed, there were 2 (two) hypotheses that were rejected and 5 (five) hypotheses accepted, with the following details, learning motivation has a positive and significant effect on learning independence, as well as learning motivation mediated by self-efficacy has a positive and not significant effect, facilities and infrastructure have a positive and significant effect on learning independence, facilities and infrastructure mediated by self-efficacy have a positive and significant effect, family environment has a positive and significant effect on learning independence, environment family mediated self-efficacy has a positive and significant effect. Furthermore, self-efficacy has a positive and not significant effect on learning independence.